Alone in the wilderness—Cultural perspectives to the participants' motives and values from participating in a danish reality TV-show - Andkjær, Søren; Ishøi, Astrid (Frontiers in Sports and Active Living, 2023)
This paper focus on the participants in the Danish version of the reality TV-show Alone, named Alone in the wilderness (AIW), and seeks to explore What motives and values are important to the participants in the TV-show (AIW) and how can the show be understood as a cultural phenomenon? The study is qualitative with a design based on a triangulation of different methods: single interviews, transcripts of programs and autoethnographic notes. The analysis is inspired by a hermeneutic approach applying a 6-phased thematic analysis. The participants motives and values from their participation in the TV-show reflect ideas that may be related to the solo experience. On one hand the participants are motivated by the challenges of being alone in the wilderness and they value the possibility of personal development. On the other hand, they value nature and simple life in the outdoors, an experience that seems to grow more important to the participants as time goes. AIW is a competition and some of the participants are highly competitive aiming at winning the show, which however becomes less important during their stay in the wilderness. AIW as a cultural phenomenon reflects ideas and values related to an understanding of adventure and the Nordic tradition of friluftsliv (simple life in the outdoors) and can be related to theories on late modernity focusing on reflectivity and self-identity. The study presents new empirically based knowledge on the motives, values and experiences of people participating in AIW and it presents new theoretically based knowledge on how these motives, values and experiences can be understood as part of outdoor education and recreation and as a cultural phenomenon in late modern society.